Excitation and deexcitation dynamics of excitons in a GaN film based on the analysis of radiation from high-order states. (12th May 2016) - Ishitani, Yoshihiro; Takeuchi, Kazuma; Oizumi, Naoyuki; Sakamoto, Hironori; Ma, Bei; Morita, Ken; Miyake, Hideto; Hiramatsu, Kazumasa
Abstract: The physical mechanism of excitation and deexcitation transitions of nonthermal exciton states in a GaN film is investigated at a measurement temperature of 23 K by time-resolved photoluminescence (PL) analysis involving phonon replica lines of the principal quantum number n   =  2 in addition to n   =  1 and bound states of the A exciton. A time region of 280 ps after a pulse excitation is mainly analyzed. The emission intensities of the constituent lines are obtained by spectrum fitting. Although the effective exciton temperature of the n   =  1 state shows a relaxation time within approximately 150 ps as a previous report, the temperature of the n   =  2 state is found to have a longer relaxation time. This is because the n   =  2 state strongly couples with the continuum by excitation and deexcitation transfers, while the n   =  1 state couples with the donor bound state. These two systems exhibit different dynamic properties. Overall population transfer is the direction of energy relaxation, however, cooling of the upper states is delayed when compared to the lower states by the increase in the excitation transfer rate to the continuum. This dynamics of the exciton has a similarity to that of hydrogen atoms in plasma.